Waste and the neoliberal work of blame: Reading politics from Cape Town’s informal landscapes - Angela D. Storey (Archivio Antropologico Mediterraneo)
Nearly one quarter of Cape Town’s population lives in informal settlements, sites characterized by limited access to basic infrastructure. This article examines how local experiences with waste management reinforce resident understandings of squatted sites as political and material landscapes, emphasizing the structural and spatial foundations of persistent exclusion. Such local understandings are set against the municipality’s neoliberal framing of resident interactions with waste and infrastructure as irresponsible and illegal, implying that residents are to blame for service limitations and using this to justify further restrictions. Drawing from public service campaigns and ethnographic research, this article examines neoliberal ideologies as discourses of blame that erase the political context for marginalized lives, and argues for the need to understand ideologies of governance by setting them against the broad politics of everyday life.